Comparison of Three Electromechanical Oscillation Damping Estimation Methods - Jukka,T; Thambirajah,J; Larsson,M; Pal,BC; Thornhill,NF; Haarla,LC; Hung,W; Carter,A; Rauhala,T (IEEE Transactions on Power Systems, 2011)
This paper describes three data driven methods to monitor electromechanical oscillations in interconnected power system operation. The objective is to compare and contrast the performance of the methods. The accuracy of damping ratio and frequency of oscillations are the measures of the performance of the algorithms. The advantages and disadvantages of various techniques and their limitations to measurement noise have been considered while assessing performance. The target frequency and damping are computed using the Nordic power system simulation model.